PERBANDINGAN BIAYA PEMERIKSAAN LABORATORIUM PADA PASIEN TUBERKULOSIS MULTIDRUG RESISTANCE (TB-MDR) DENGAN TUBERKULOSIS EXTENSIVE DRUG RESISTANCE (TB-XDR): STUDI PADA RUMAH SAKIT TERSIER DI BANDUNG - Raja Iqbal Mulya Harahap; Juandika Juandika; Dety Mulyanti (DIAGNOSA: Jurnal Ilmu Kesehatan dan Keperawatan, 2023)
Introduction. Tuberculosis (TB) is one of the oldest diseases known to attack humans, caused by the bacterium Mycobacterium tuberculosis. Multi-drug-resistant TB (MDR-TB) is a stage or condition in which Mycobacterium tuberculosis becomes minimally resistant to rifampicin administration and also insonicotinylhydrazine (INH). Extensive-drug-resistant TB (XDR-TB) is an MDR-TB with Mycobacterium tuberculosis immune characteristics against one of the fluoroquinolone class drugs and one of the second-line injection OAT (capreomycin, kanamycin, and amikacin). The aim of this study was to find out the description of variation in laboratory costs of MDR-TB/XDR patients on one treatment cycle. Method. The inclusion criteria were patients who had been diagnosed with MDR-TB/XDR and performed laboratory tests. The design of this study was a cross-sectional retrospective analytics using medical records of MDR-TB/XDR patients in MDR division. Results. There were 30 MDR-TB research subjects and 2 XDR-TB research subjects examined for laboratory examination. Comparison of laboratory mean of MDR-TB/XDR (p = 0,018). Discussion. There was a significant difference in the total cost of MDR-TB/XDR laboratory examinations in one treatment cycle. Conclusion. Laboratory examination of MDR-TB/XDR patients requires considerable cost, this is due to the side effects of OAT that require patient clinical monitoring.